2018
DOI: 10.1590/0034-7167-2017-0824
|View full text |Cite
|
Sign up to set email alerts
|

Educational technology for people living with HIV: validation study

Abstract: the technology presents high reliability and good internal consistency, being deemed appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
23

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 14 publications
0
5
0
23
Order By: Relevance
“…O envio via e-mail do material de avaliação, juntamente com a tecnologia educativa, proporcionou a inserção de juízes de estados das diferentes regiões brasileiras, incluindo as experiências e realidades vivenciadas nos diferentes contextos regionais. Essa estratégia também foi utilizada por outros autores (10) na construção de materiais educativos impressos, como cartilhas e álbuns seriados, com a finalidade de englobar as diversidades culturais, contribuindo para maior aplicabilidade e credibilidade do material nas diversas localidades do país.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…O envio via e-mail do material de avaliação, juntamente com a tecnologia educativa, proporcionou a inserção de juízes de estados das diferentes regiões brasileiras, incluindo as experiências e realidades vivenciadas nos diferentes contextos regionais. Essa estratégia também foi utilizada por outros autores (10) na construção de materiais educativos impressos, como cartilhas e álbuns seriados, com a finalidade de englobar as diversidades culturais, contribuindo para maior aplicabilidade e credibilidade do material nas diversas localidades do país.…”
Section: Discussionunclassified
“…O número de juízes seguiu a recomendação (8) de seis a vinte especialistas, também utilizado em outros estudos com validação de materiais educativos na área da saúde (7)(8)(9) . A seleção destes ocorreu pelo método de amostragem de rede ou bola de neve (10)(11) .…”
Section: Métodosunclassified
“…As for the context and type of technology developed in the PM, it was found that the main technology to live with the disease (20) .…”
Section: Discussionmentioning
confidence: 99%
“…By measuring these aspects, we meet the scientific rigor required in the validation processes. 11,21,22 As for the technology being a tool that enables the understanding of tuberculosis, the semantic validation showed the importance of carefully choosing the words that allow an understanding compatible with the lay public and age group. This aspect is important, considering that, in the health area, information is often disclosed in technical language, which makes it difficult for the target audience to understand, especially when dealing with different groups, such as children or people with special needs.…”
Section: Educational Technology On Tuberculosismentioning
confidence: 99%